The Value of the Benefits of Mangrove Ecosystems in the Village of Pulau Cawan, Mandah, Indragiri Hilir District - Nurul Aulia; Trisla Warningsih; Deni Efizon (Jurnal Perikanan dan Kelautan, 2023)
The purpose of this study is to know the value of an economic benefit of the total mangrove forest located in the village of Pulau Cawan Indragiri Hilir regency, namely using the concept of valuation economic in calculating the benefits of mangrove existence that has the potential of existing natural resources. This research was conducted in August 2020, The observations made in the field use observations and direct interviews with the local government and the community around the village of Pulau Cawan. The results of the research obtained showed the ecosystem of the mangrove forest area of the village of Pulau Cawan which has an area of ±3,401.66 ha, and there is a value of existing benefits of IDR 21.200.000 ha/year. The factors that will affect the willingness to pay (WTP) of the community around mangrove forests in the form of the respondent's income level, the respondent's education level, the respondent's gender, the respondent's age, and the respondent's family dependents. The benefit value of the existence of The Village of Pulau Cawan can be used as a basis for decision-making by the local government and the surrounding community in the management of policies and utilization of mangrove forests in maintaining and preserving mangrove forest ecosystems for the sustainability of the future with the results obtained in knowing the existence of the value function of a mangrove ecosystem, it can result in the formulation of the mangrove forest conservation reserve area of Pulau Cawan village, namely the implementation and development of the “Ecu-Edu Wisata Mangrove” (EEWM) concept plan.